The impact of sociodemographic factors on academic achievements among high school students in Indonesia - Deri Indrahadi; Amika Wardana (Institute of Advanced Engineering and Science, 2020)
This study aimed to examine the effect of sociodemographic, student and school factors on the academic achievement of high school students in Indonesia. Using the cross-sectional survey data from the 2015 Indonesian Family Life Survey (IFLS) particularly involving 1,421 respondents (of the academic performances during their school years), the study run multiple regression analysis to examine the influences of their parents’ sociodemographic, students and other school-related factors on their academic achievements during their school years. As the results, it was revealed that the sociodemographic factors, students and schools predict significantly academic achievement of students in Indonesia. The results provided feedback to students and parents, schools and education policymakers in improving student academic achievement.